Unraveling the Relationship between Business Strategy and Shareholder Value Maximization - Mulyani, Yani (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study aims to explore the relationship between business strategy and shareholder value maximization, focusing on the mechanisms that drive value creation and sustainability in the global marketplace. It seeks to integrate various theoretical perspectives and empirical evidence to enhance understanding in this area. Research Design and Methodology: The thematic analysis and narrative synthesis reveal key themes and theories that contribute to understanding the formulation of business strategy and its impact on shareholder wealth. The findings emphasize the importance of strategic consistency, resource endowments, and stakeholder engagement as key drivers of financial performance and value creation. Findings and Discussion: The study highlights the need for further research to adapt to emerging trends and practical challenges in strategic management and corporate governance. It contributes to ongoing discussions in the field, providing valuable insights for scholars, practitioners, and organizational leaders, and highlights the practical implications of effectively implementing business strategies to maximize shareholder value. Implications: The study emphasizes the importance of continuous adaptation and innovation in accounting practices for effectively navigating evolving business environments. Moreover, technological advancements, globalization, and regulatory reforms have a significant impact on accounting practices and organizational dynamics, presenting both opportunities and challenges.